Pengaruh Kepemimpinan dan Disiplin Terhadap Kinerja Karyawan Pada PT.PELINDO Cabang Belawan - Arianty, Nel (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
Leadership is one of the factors that shape and help others to enthusiastically work and achieve the planned object in relation to the success of the organization realize the objectives are largely determined by the high performance leadership and employed in carrying out their duties. Problems that exist in the company are leaders in their duty to behave authoritarian that provide employment to its employees at will without doing approaches that can stimulate employees to work well so that the performance of the employees to be ineffective.Â